Intestinal ciliate fauna of the Asian elephant from Gaziantep, Turkey and the description of Brevitentaculum antebum n. g., n. sp. - Gürelli, Gözde (Elsevier BV, 2016)
The aims of this investigation were to identify and quantify ciliates inhabiting the large intestine of Asian elephants living in Gaziantep Zoo, Turkey, and to describe a new suctorian genus and species. Species composition and distribution of intestinal ciliates voided in the feces of two Asian elephants were examined. Fifteen species of intestinal ciliates, representing 7 genera, were identified. One new suctorian genus and species, Brevitentaculum antebum n. g., n. sp., was described. This new species has two short truncated terminal projections, with two longitudinally lined bands located between the two projections, near the convex surface of the cell. Short clavate-like tentacles are in two fascicles near each base of terminal projections on the flattened surface of the body. Ciliate densities in the two fecal samples were 4.5×104mL-1 and 10×104mL-1.
Keywords: Intestines; Feces; Species Specificity; Turkey; Elephants; Animals; Biodiversity; Ciliophora; 13. Climate action; 7. Clean energy